2020
DOI: 10.1039/c9tc05357c
|View full text |Cite
|
Sign up to set email alerts
|

Inducing formation of a corrugated, white-light emitting 2D lead-bromide perovskite via subtle changes in templating cation

Abstract: A corrugated (110)-oriented 2D Pb–Br perovskite was obtained by systematic modulation of templating dication structure. Upon excitation by UV light, this material exhibits intrinsic “cold” white light emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 31 publications
4
56
0
Order By: Relevance
“…In particular, in contrast to 1[PbI 3 ], 2[PbI 3 ]s hows greaterd ifferences between the length of the PbÀIb onds mutually trans to one another along two of the three coordination axes (Table S1 in the Supporting Information). Quantitatively, the degree of "intra-octahedral" distortions can be assessed by comparing the following, previously reported, parameters (see Table S2 in the Supporting Information for details): [40][41][42][43] octahedral elongation (l oct ), octahedral angle variance( s 2 oct ), and octahedral bond length distortion (D oct ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, in contrast to 1[PbI 3 ], 2[PbI 3 ]s hows greaterd ifferences between the length of the PbÀIb onds mutually trans to one another along two of the three coordination axes (Table S1 in the Supporting Information). Quantitatively, the degree of "intra-octahedral" distortions can be assessed by comparing the following, previously reported, parameters (see Table S2 in the Supporting Information for details): [40][41][42][43] octahedral elongation (l oct ), octahedral angle variance( s 2 oct ), and octahedral bond length distortion (D oct ).…”
Section: Resultsmentioning
confidence: 99%
“…[5,21] Recent studies report more examples of bluish-white and bright white emitting RPLP, which are mostly investigated through halide ion modifications (i.e., Cl − , Br − , and I − ) [22,23] and by using diverse organic molecules. [17,[24][25][26]27] In general, RPLP have a (100)-oriented structure that typically exhibits a narrow emission in the deep blue region, with few cases showing white emission; or they can have a (110) crystal orientation (so called corrugated structures), which display cold, warm, or pure white CRI. [2,6,17,27,28] Current challenges include control over layer thicknesses, thermal stability, reduced lattice defects and self-quenching, to improve their so far limited quantum efficiency (≈9% [23] from white-light-emitting bulk single crystals, which has been increased up to 12% [29] from microplates of less than 2 µm lateral size obtained through a slow crystallization in toluene).…”
Section: Introductionmentioning
confidence: 99%
“…[17,[24][25][26]27] In general, RPLP have a (100)-oriented structure that typically exhibits a narrow emission in the deep blue region, with few cases showing white emission; or they can have a (110) crystal orientation (so called corrugated structures), which display cold, warm, or pure white CRI. [2,6,17,27,28] Current challenges include control over layer thicknesses, thermal stability, reduced lattice defects and self-quenching, to improve their so far limited quantum efficiency (≈9% [23] from white-light-emitting bulk single crystals, which has been increased up to 12% [29] from microplates of less than 2 µm lateral size obtained through a slow crystallization in toluene). In view of the rich variety of organic molecules that is available, the material design possibilities toward optoelectronic technologies have only been explored to a very small extent.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Early on, broadband emission was linked to Pb-Br perovskites bearing comparatively rare corrugated (110)-oriented structures. 1,2,7,8,11,19 Later, more common (100) Pb-Br variants, which typically emit narrow freeexcitonic (FE) PL in the blue or near-UV region, were also found to exhibit similar broad PL features, albeit with a strong dependence on temperature. In particular, Smith et al suggested a correlation between greater out-of-plane interoctahedra distortions of the crystal lattice in (100) Pb-Br perovskites and increased relative intensity of broadband emission.…”
mentioning
confidence: 98%
“…5 Recent works have allowed compilation of a library of these compounds, leading to the development of further broadband emitting metal halides along with the understanding of how these properties can be induced. 1,2,[6][7][8][9][10][11] Figure 1. The organic dications, 1 and 2, used in this study.…”
mentioning
confidence: 99%